The internet and democracy : the casual link between technology and politics - Weare, Christopher (2002)
This paper strives to explicate the causal links between changing technology and democratic governance. Its over-arching goal is to define the relevant concepts of communication and governance and more importantly, to focus empirical observations on the critical dimensions of a multifaceted phenomenon. The analysis focuses on three key links in this causal chain. The first is the effects of technological innovation on different communication activities. The second link involves the role communication and information play in democratic governance. The final is the social and political mechanisms by which technological innovations are introduced within and transform democratic processes and institutions. We argue that a sharper understanding of these three essential links will enable the growing numbers of researchers interested in electronic democracy to employ the massive social experiment the Internet represents to clarify and further democratic theory itself. - Reproduced.
Keywords: Internet